Persuasive Strategy On Advertising Slogan On Instagram "Wardah" Cosmetic - Devi, Sanita (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This study deals with the analysis of Persuasive Strategies Used in SloganWoman Cosmetics Wardah Advertisement on Instagram. Wardah is the onefamous brand of the beauty from local brand and also every woman use theproduct of Wardah. It is be a reason why the researcher use a Wardah as anobject in the product can be the research. Wardah product has a several sloganin to advertising their product. The objectives of this research is to identify thekinds of persuasive strategies and describe the way or modes persuasivestrategy used in slogan advertisement of Wardah Cosmetics. Qualitativeresearch is applied to analyze the data. That the qualitative research is focusedon analyzing the data in the form of words, and not about numerical data. Theresearcher is used 14 slogan advertisement on official account Wardah onInstagram. In collecting the data the researcher browsed the sloganadvertisement by search on Wardah official account on Instagram, and then theresearcher chosen the slogan advertisement of Wardah to be analyzed. Thenext, the researcher identified the slogan, understanding what the kinds ofpersuasive strategies used in the slogan and the way or modes to persuadeconsumers. The result of the data analysis show the researcher found andanalyzed. The types of persuasive strategies, there are: rationalization (5 data),identification (7 data), suggestion (11 data), conformity (5 data) andcompensation (3 data). And the way to persuade consumers, those are: ethos (7data), pathos (2 data) and logos (5 data).